2013
DOI: 10.2486/indhealth.2012-0059
|View full text |Cite
|
Sign up to set email alerts
|

A Single-item Global Job Satisfaction Measure Is Associated with Quantitative Blood Immune Indices in White-collar Employees

Abstract: Although a single-item job satisfaction measure has been shown to be reliable and inclusive as multiple-item scales in relation to health, studies including immunological data are few. The purpose of this study was to evaluate the validity of single-item job and family life satisfaction based on its association with immune indices. A total of 189 white-collar employees (70% men) underwent a blood draw for the measurement of natural killer (NK), total T, and B cell counts as well as plasma immunoglobulin (Ig) G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…It is possible that a long set of items may lead respondents to evaluate aspects of their job that would otherwise be marginal to their overall evaluation. A final advantage offered by the adoption of general single-item measures of job satisfaction is that they overcome the issue of job-specific measures given that they measure generic job satisfaction ( Nakata, Irie, & Takahashi, 2013 ).…”
Section: The Teacher Job Satisfaction Scale: Developing the Questionnmentioning
confidence: 99%
“…It is possible that a long set of items may lead respondents to evaluate aspects of their job that would otherwise be marginal to their overall evaluation. A final advantage offered by the adoption of general single-item measures of job satisfaction is that they overcome the issue of job-specific measures given that they measure generic job satisfaction ( Nakata, Irie, & Takahashi, 2013 ).…”
Section: The Teacher Job Satisfaction Scale: Developing the Questionnmentioning
confidence: 99%
“…Among many occupational stress-related factors, internal input can lead to occupational stress, resulting in increased synthesis of catecholamines and increased levels of free fatty acids and glucagon in the blood (18). Occupational stress has an inhibitory effect on the body's humoral immune function, and the content of IgG and IgA decreases with the increase of occupational stress (6,19). However, the levels of IgG and IgA in the serum of highly stressed people are significantly higher than those in the control group, and occupational stress is positively correlated with the level of immune function (20).…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization calls occupational stress a worldwide epidemic. Studies have shown that (1)(2)(3)(4)(5)(6)(7), the human body in a state of tension may show a series of physiological, biochemical, endocrine, metabolic and immune function changes. In recent years, domestic and foreign scholars have carried out research on the effects of occupational stress on cardiovascular diseases, metabolic diseases and immune system diseases for typical occupational groups such as police and teachers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunological biomarkers have been reported to be associated with job-related stress ( 10 ). A single-item global job satisfaction measure may be a valid tool to evaluate immune status in healthy white-collar employees ( 11 ).…”
Section: Introductionmentioning
confidence: 99%